Melatonin Versus Chloral Hydrate for Sleep Electroencephalography Recording in Children: A Comparative Study Using Bispectral Index Monitoring Scores and Electroencephalographic Sleep Stages. Issue 7 (16th November 2022) - Yilmaz, Sanem; Simsek, Erdem; Gazeteci Tekin, Hande; Aktan, Gul; Gokben, Sarenur; Tekgul, Hasan
Abstract : Purpose: To compare the effects of chloral hydrate and melatonin on sleep EEG recordings in children by using standard EEG sleep stages and the bispectral index scores (BIS). Methods: A total of 86 children were randomly assigned to two groups: (1) melatonin group (n = 43) and (2) chloral hydrate group (n = 43). BIS monitoring scores and sleep EEGs were recorded simultaneously. The effect of two drugs on sleep EEG recording was evaluated with sleep stages of EEG and BIS. Results: There was no statistically significant difference between the groups with regard to time to sleep onset and the need for a second drug ( P = 0.432; P = 1.000). Eight patients (18.6%) in chloral hydrate group reported side effects while there were no reported side effects in the melatonin group ( P = 0.006). Mean BIS values during EEG recordings were similar in both groups (59.72 ± 18.69 minutes and 66.17 ± 18.44 minutes, respectively, P = 1.000). The average time to achieve N2 sleep was 32.38 minutes in the chloral hydrate group and 43.25 minutes in the melatonin group ( P < 0.001). Both "time spent in wakefulness" and "N1 sleep" were found to be significantly higher in the melatonin group ( P < 0.001 and P = 0.005). BIS scores higher than 75 were found to be suggestive for wakefulness; 75 to 66 for N1, 65 to 46 for N2, and values lower than 46 were found to be indicative for N3 sleep with a good strength of agreement in weighted Kappa analysis (95% confidence interval; weighted Kappa = 0.67). Conclusions: Melatonin is reliable and at least as effective as chloral hydrate for sleep EEG acquisition in children.